2003
DOI: 10.1073/pnas.0732111100
|View full text |Cite
|
Sign up to set email alerts
|

A global view of the selectivity of zinc deprivation and excess on genes expressed in human THP-1 mononuclear cells

Abstract: Among the micronutrients required by humans, zinc has particularly divergent modes of action. cDNA microarray and quantitative PCR technologies were used to investigate the zinc responsiveness of known genes that influence zinc homeostasis and to identify, through global screening, genes that may relate to phenotypic outcomes of altered dietary zinc intake. Human monocytic͞ macrophage THP-1 cells were either acutely zinc depleted, using a cell-permeable zinc-specific chelator, or were supplemented with zinc to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
133
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(145 citation statements)
references
References 37 publications
7
133
4
Order By: Relevance
“…In contrast to mZip4, little regulation of mZIP1 or mZIP3 mRNA levels by zinc status has been observed (19,22,24). These observations led us to investigate whether the activity of these proteins was regulated at a post-translational level.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to mZip4, little regulation of mZIP1 or mZIP3 mRNA levels by zinc status has been observed (19,22,24). These observations led us to investigate whether the activity of these proteins was regulated at a post-translational level.…”
Section: Figmentioning
confidence: 99%
“…In mammals, regulation of some zinc uptake transporters occurs at the level of mRNA abundance possibly via transcriptional control. For example, SLC39A2 (hZIP2) mRNA levels rise almost 30-fold in cultured THP-1 monocytes made zinc-deficient by treatment with TPEN, a membrane-permeable zinc chelator (22). Similarly, mice fed a zinc-deficient diet accumulate ϳ10-fold more mZIP4 mRNA in intestinal enterocytes than is found in zinc-replete animals (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that MTF-1 controls the expression of many more important genes in addition to MT-I and MT-II Andrews et al, 2001). Very recently, MTF-2, an ortholog of MTF-1, was identified as another zinc-dependent transcription factor (Cousins et al, 2003). There appears to be a huge number of 'zinc-regulated' genes in all organisms and it remains to be determined how zinc availability in a cell controls target gene transcription directly or secondarily by indirect mechanisms (Beyersmann and Haase, 2001).…”
Section: Zinc Participates In Gene Expression Controlmentioning
confidence: 99%
“…It was reported that zinc deprivation and excess affect gene expression in human THP-1 mononuclear cells (Cousins et al 2003). But it remained unclear how exactly and how much zinc ions replaced rHI functions in cell culture.…”
Section: Importance Of Zinc For Culture Growth and Formulation Of Promentioning
confidence: 99%